Factors associated to the correct practice of breast self examination. - Manrique-Abril, Fred Gustavo; Ospina-Diaz, Juan Manuel; Vega Fuentes, Nancy Astrid; Morales Pacheco, Adriana Lisset; Herrera Amaya, Giomar Maritza (Investigación y Educación en Enfermería, 2025)
Objective. To determine the factors associated with the correct execution of breast self examination (BSE) in adult women from Tunja, Boyaca (Colombia). Methodology. Cross sectional epidemiological study, carried out in 2009 using a multi-stage randomized stratified sampling. 810 women were chosen and a survey about frequency, opportunity and technique used in the execution of the BSE was applied. Results. Life prevalence of the BSE execution was just 27.8%, out of which just 6.2% had a correct technique. The main factors found significantly associated with the correct execution of BSE were: Having learned and mechanized a regular and systematic technique, secondary or higher education, and having knowledge about breast cancer. Conclusion. The prevalence of BSE is low in the studied women, in just a little percentage it is done correctly. Strengthening education in health and motivating women to make it an opportune and regular practice are some of the actions should be considered in the health organizations.